Stakeholder Perceptions of Artificial Intelligence in the Indonesian Film Industry - Hartanto, Louisa Christine; Pascarina, Patrisia Amanda; Haryono, Cosmas Gatot (JURNAL KOMUNIKASI INDONESIA, 2026)
This study explores how stakeholders in the Indonesian film industry perceive the emergence and use of artificial intelligence (AI). Framed by Roger's Diffusion of Innovation theory, this study explores how artificial intelligence (AI) is positioned as an emergent technological innovation, spreading via communication channels across the film industry's social ecosystem. This approach illuminates how distinct categories of adopters collectively construct the meaning of AI and shape their varied responses to its encroachment on creative labour. Employing a qualitative descriptive approach, the study draws on data from two Focus Group Discussions involving directors, actors, government experts, academics, emerging filmmakers, students, and film festival organizers. Thematic analysis identified three key themes: AI adaptation across the innovation adoption spectrum, the tension between productivity and artistic work, and AI as a catalyst for new job creation. The findings indicate that although AI offers substantial gains in efficiency, stakeholders consistently view human creativity, emotional authenticity, and artistic expression as irreplaceable. This study contributes to understanding AI integration in creative industries from the perspective of practitioners in the Global South. These findings offer new insights by demonstrating that AI integration in the creative industries of the Global South is not merely a technical transition but a complex negotiation of creative values and artistic control. The study implies that future policies should focus on developing inclusive human-AI collaboration models that prioritize originality and protect the intellectual property rights of film practitioners. Keywords: artificial intelligence, film industry, stakeholder perceptions, qualitative research